Tao-1 phosphorylates Hippo/MST kinases to regulate the Hippo-Salvador-Warts tumor suppressor pathway. - Boggiano, J.C.; Vanderzalm, P.J.; Fehon, R.G. (Developmental Cell, 2011)
Recent studies have shown that the Hippo-Salvador-Warts (HSW) pathway restrains tissue growth by phosphorylating and inactivating the oncoprotein Yorkie. How growth-suppressive signals are transduced upstream of Hippo remains unclear. We show that the Sterile 20 family kinase, Tao-1, directly phosphorylates T195 in the Hippo activation loop and that, like other HSW pathway genes, Tao-1 functions to restrict cell proliferation in developing imaginal epithelia. This relationship appears to be evolutionarily conserved, because mammalian Tao-1 similarly affects MST kinases. In S2 cells, Tao-1 mediates the effects of the upstream HSW components Merlin and Expanded, consistent with the idea that Tao-1 functions in tissues to regulate Hippo phosphorylation. These results demonstrate that one family of Ste20 kinases can activate another and identify Tao-1 as a component of the regulatory network controlling HSW pathway signaling, and therefore tissue growth, during development.